Investigation on the RCCI engine on performance and emission - Ahmad Fitri, Yusop; Mohamad Adzuan, Aziz; Mohd Adnin, Hamidi; Daing Mohamad Nafiz, Daing Idris; Ummi Hafsah, Zaidi (ISRES Publishing, 2022)
RCCI engine is among the most promising combustion technology for the upcoming generation of heavy-duty motors. In RCCI mode combustion, different combinations of low reactivity fuels (LRF) and high reactivity fuels (HRF) such as PRF-Diesel, can be used to achieve a chemical reaction or reactivity stratification in the engine combustion chamber. The high reactivity fuel (HRF) which is diesel will be injected in the direct fuel injection and the low reactivity fuel (LRF) which is Primary Reference Fuel (PRF) will be injected in port fuel injection. Combustion in the engine combustion chamber will convert the chemical energy of fuels to heat that can be used directly or further converted to mechanical energy. Internal combustion engine outputs mechanical power by extracting energy in fuels via combustion reaction in the cylinders. Fuels are burned in the combustion chambers to generate high temperature and high-pressure gas which delivers power to the piston. RCCI had a low performance at high engine speed due to its high tendency on knocking and high pressure rise rate. Therefore, this study investigates the effect of the fuel stratification on the RCCI combustion and it’s extended to the interaction of high and low reactive fuels, PRF and diesel in the RCCI combustion system. Modified engine was tested for engine performance. The change in BSFC, Power and Torque are observed at all loads and speeds with different PRF percentages. For emissions, this RCCI engine was said to produces extremely low in nitrogen oxide. On a regular diesel engine, these kinds of pollutants cause problems. The cool burning, on the other hand, does not emit nitrogen oxide when using an RCCI engine. Aside from that, because the RCCI engine uses less diesel fuel, the diesel fuel has more time to mix in the cylinder.